กระบวนการขับเคลื่อนสถานศึกษาขั้นพื้นฐานสู่ประชาคมอาเซียน - เขียวน้อย(Kajornsak Khiawnoi) ขจรศักดิ์; อินทรกำแหง(Ungsinun Intarakamhang) อังศินันท์; อยู่ในศิล(Waiyawut Yoonisil) วัยวุฑฒ์ (Journal of Behavioral Science for Development, 2016)
(A Process of Driving Basic Education Schools to the ASEAN Community) Abstract The purposes of this study were 1) to understand and to describe the meaning of Driving Basic Education Schools to the ASEAN Community of school administrators and stakeholders in master schools, 2) to examine good practices for Driving Basic Education Schools to the ASEAN Community. In-depth interviewed and focused group of 6 school administrators and 16 stakeholders are used as qualitative methodology. The findings are as follows: 1. A Driving Basic Education Schools to the ASEAN Community is a way of making awareness, participation, and contribution to the success of the changes. Consisting of 1) Establishing a Sense of Urgency, 2) Creating the Guiding Coalition, 3) Developing a Vision and Strategy, 4) Communicating the Change Vision, 5) Empowering Broad-Based Action, 6) Generating Shot-Term Wins, 7) Continuous Improvements, and 8) Institutionalizing ASEAN School Successful. 2. A Driving Basic Education Schools to the ASEAN Community should focus on staff development. This can be done by stimulating them to have a widely defferent thinking. Students should also be encouraged to be population of not just country but also ASEAN. They should also be enhanced on the skill, this can be included attitude and performance, language skill and learning how to live on a changing basis and so forth. There must be a leadership of each school who can pay attention on bring it into socialization and focus on self identity. Moreover, specifying ASEAN Curriculum Sourcebook is a must. Keywords: ASEAN Community, Driving Basic Education Schools